Strategi Pemenangan Politik (Studi Pemenangan Made Muliawan Arya dalam Pemilihan Legislatif Kota Denpasar 2019) (Jurnal Nawala Politika, 2022)
This research aims how to find out the political strategy of Made Muliawan Arya (De Gadjah) in the 2019 legislative elections. This study is framed using theory of political strategy as an analytical tool in research and conventional media concepts as a comparison. The research method used in this research is qualitative descriptive. The results of this study are: first, conventional media assisted De Gadjah in forming a mass base down to the grassroots, before social media was widely used in political campaigns. Second, social media in political campaigns helped De Gadjah in expanding the reach of voters and providing more variety in creating campaign content. Third, De Gadjah uses social media as a place to communicate and express aspirations.